Terminal Cyclohexane-Type Meroterpenoids from the Fruiting Bodies of Ganoderma cochlear - Qin, Fu-Ying; Xu, Te; Li, Yan-Peng; Zhang, Hao-Xing; Cai, Dan; Liu, Li-Zhong; Cheng, Yong-Xian (Frontiers in Chemistry, 2021)
Eleven new cyclohexane-type meroterpenoids (1, 3–5, 7, 8, 11–15) and four known similar meroterpenoids (2, 6, 9, and 10) were isolated from Ganoderma cochlear. Their structures and absolute configurations at stereogenic centers were elucidated by using HRESIMS, NMR spectroscopy and computational methods. In addition, the structure of the known meroterpenoid, cochlearol G (2), was revised, and the absolute configurations at the stereogenic centers of known meroterpenoids 9 and 10 were determined. All the isolated meroterpenoids were evaluated for their activities against renal fibrosis and triple negative breast cancer, and their insulin resistance. The results of the renal fibrosis study showed that meroterpenoid 11 inhibits over-expression of fibronectin, collagen I and α-SMA. Results of the wound healing study revealed that 4, 6 and 8 significantly inhibit migration of BT549 cells. Observations made in Western blotting experiments showed that 6 decreases the levels of TWIST1 and ZEB1, and increases the level of E-cadherin. Finally, meroterpenoids 7, 9, 11, and 15 significantly up-regulate p-AMPK protein expression in normal L6 myotubes cells.